2017
DOI: 10.1080/08820538.2017.1301968
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Erectile Dysfunction in Males with Central Serous Chorioretinopathy

Abstract: CSCR patients experience a higher incidence of sexual dysfunction compared to healthy individuals without CSCR. The exclusion of confounding factors suggests that factors involved in CSCR pathogenesis may also play a role in ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…In accordance with this study, Kim YK et al (2018) found that acute CSC, but not chronic CSC, is associated with depression symptoms assessed by BDI, the severity of depression showed a linear correlation with the size of the choroidal lesion in this group [21]. Moreover, sexual satisfaction was higher in acute CSC than chronic CSC subgroup [25].…”
Section: Csc Patients /supporting
confidence: 78%
See 1 more Smart Citation
“…In accordance with this study, Kim YK et al (2018) found that acute CSC, but not chronic CSC, is associated with depression symptoms assessed by BDI, the severity of depression showed a linear correlation with the size of the choroidal lesion in this group [21]. Moreover, sexual satisfaction was higher in acute CSC than chronic CSC subgroup [25].…”
Section: Csc Patients /supporting
confidence: 78%
“…Sexual desire score, evaluated with the 15-question Index of Erectile Function-15 (IIEF-15), was negatively associated with CSC duration. No BDI and BAI results were reported [25]. Uhumwangho et al (2015) described a cases series of five CSC patients.…”
Section: Csc Patients /mentioning
confidence: 99%